Two decades after Salini v Morocco: The case for retaining the Salini test with modifications - CHAN, Darius (Institutional Knowledge at Singapore Management University, 2023)
The definition of an investment under Article 25 of the ICSID Convention continues to attract a divergence of views. Ever since its use in 2001, the Salini Test, in its various forms, has become the predominant method that tribunals use to determine whether there is an investment. However, the Salini Test is hardly free from controversy, and suffers from two significant issues. First, its criteria are often subject to differing interpretations, leading to confusion over how the test should actually be applied. Second, the Salini Test has lost its legal force over time, as it has been relegated to factors that are ‘typical characteristics of an investment’ rather than jurisdictional requirements, of which the latter is arguably its proper role as part of a ‘double-keyhole’ test. This article addresses these issues by taking a detailed look at the individual criteria of the Salini Test and its original purpose. It proposes that (i) the Salini Test remains the best method for determining the meaning of ‘investment’ in Article 25 of the ICSID Convention, and (ii) regardless of whether the Salini Test is jurisdictional requirements or indicative factors, its individual criterion is in urgent need of refinement due to their inconsistent usage.